Pengembangan LKPD Berbasis Creative Problem Solving (CPS) Pada Pembelajaran Tematik Terpadu untuk siswa kelas IV SD - Lika Putri Mulia; Mai Sri Lena (Universitas Mathla'ul Anwar Banten, 2021)
This study aims to develop Creative Problem Solving (CPS) based LKPD on integrated thematic learning for grade IV students of SDN 02 Minangkabau that is valid and practical. This research includes a type of development research (R&D) using addie development model consisting of analysis stage, design stage, development stage, implementation stage, assessment stage. This research was conducted in the even semester of the 2020/2021 school year. The subjects of this study were 3 experts (material experts, linguists, and graffiti experts), 1 grade IV teacher, and 17 fourth graders. The instruments used in this study are expert validation sheets, questionnaires of teacher and student responses. The results showed: (1) LKPD based on Creative Problem Solving ( CPS) in integrated thematic learning for grade IV students of SDN 02 Minangkabau was declared very valid by material experts, language and graphing with an average assessment of the overall validator 86, 55%, ( 2) the response of teachers and students to LKPD based creative problem solving ( CPS) on integrated thematic learning for grade IV students SDN 02 Minangkabau obtained an average teacher response score of 91. 6% with a very practical category and 93% student response with a very practical category. So it can be concluded that LKPD based on Creative Problem Solving ( CPS) is very valid and practical to be used in integrated thematic learning for grade IV elementary students.